2020
DOI: 10.1002/aenm.202002709
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsic Role of Molecular Mass and Polydispersity Index in High‐Performance Non‐Fullerene Polymer Solar Cells

Abstract: efficiencies (PCEs) rapidly improving from 11% to extend to 17% over the past five years. [9,10,11,12] However, a number of works have shown that non-fullerene PSCs also suffered from rapid performance degradation over time, particularly upon exposure to oxygen, light or elevated temperatures. [13,14,15,16] It can be seen that the development of highly efficient PSCs that show stable photovoltaic performance without adverse degradation remains a significant challenge in this field. [14] Extensive efforts are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 62 publications
3
44
0
Order By: Relevance
“…The operational stability is one of the most challenging issues for "Y-series" PSCs. Min and co-workers [47] investigated the stability of device with PM6:Y6 active layers by tuning the molecular weight (M w ) and polydispersity (PDI) of PM6. It was found that devices based on different PM6 batches retained about 40%-70% of their initial PCEs after 100 h sun illumination.…”
Section: 01×10mentioning
confidence: 99%
“…The operational stability is one of the most challenging issues for "Y-series" PSCs. Min and co-workers [47] investigated the stability of device with PM6:Y6 active layers by tuning the molecular weight (M w ) and polydispersity (PDI) of PM6. It was found that devices based on different PM6 batches retained about 40%-70% of their initial PCEs after 100 h sun illumination.…”
Section: 01×10mentioning
confidence: 99%
“…[5][6][7] Despite the success of the field of PSCs, batch-to-batch differences in molecular weight of a conjugated polymer used as one of the active layer components within a BHJ active layer, led to inconsistency in macromolecular ordering, optoelectronic and charge transport characteristics, and ultimately device performance. [8][9][10][11] There have been several attempts to overcome the molecular weight limitations caused by synthetic polymers. For example, You's and Marks's groups independently demonstrated the possibility of controlling polymer's molecular weight via a synthetic strategy based on the classic Carothers equation, considering the comonomer ratios and degree of polymerization.…”
mentioning
confidence: 99%
“…In addition, the number‐averaged molecular weight ( M n ) and polydispersity index (PDI) are also comparable, that is, 35.11 kDa/1.46 and 26.93 kDa/1.51 for P75 and PBDB–T, respectively, which minimize the impact of molecular weight on the performance. [ 47 ]…”
Section: Resultsmentioning
confidence: 99%